(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Another ways to prediction the force-displacement curve of indentation (P-h curves) from constitutive material properties has been created and assessed for Vickers Indentation. This gave a helpful apparatus to assess the possibility of utilizing hardness value in anticipating the constitutive material parameters concerning precision and uniqueness by mapping through every potential material reaches. The scale of Indentation Size Effect (ISE) can be reliably estimated and it can possibly be connected to the Hardness-to-Modulus proportion (H/E). The size of ISE of the examples tried is genuinely repeatable and the connection with material properties (e.g. H/E) is significant and reliable. Idea to utilize the space size information of the Vickers indentation has been investigated to improve the accuracy/robustness of inverse properties modelling dependent on hardness utilizing steel as material framework. The work demonstrated that there is huge ISE in the Vickers hardness tests and the scale and consistency/unwavering quality of ISE was investigated by fitting information observing the Meyer’s Power Law and the proportional specimen resistance (PSR) models. The ISE power law index displayed a sensible concurrence with the hardness-elastic modulus ratio (H/E). Another idea of utilizing ISE data for assessing the Strain hardening exponent (n) estimations of steel has been investigated and indicated sensible outcomes for narrowing the scope of anticipated material properties dependent on hardness value.